Financial Distress Analysis using Altman Z-Score and Zmijewski Methods in Oil and gas sector listed on the IDX in the 2018-2021 period - Putra, Risdi Aulia; Purnamawati, Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
Based on the research results obtained that in the Altman Z-Score method in 2018 (APEX), (ARTI), (ENRG), (ESSA), (MTFN), and (SURE), (WOWS), experienced financial distress, while according to Zmijewski the company was non distressed. In the Altman Z-Score method in 2019 the company (APEX), (ARTI), (ELSA), (ENRG), (ESSA), (MEDC), (MITI), (PKPK), (RUIS) and (SURE) are experiencing financial distress, while according to Zmijewski the company is non distressed. In the Altman Z-Score method in 2020 the companies (ARTI), (ESSA), (MEDC), and (MITI) experienced financial distress, while according to Zmijewski the company was non-distress. In the Altman Z-Score method in 2021 the companies (ARTI), (ESSA), (MEDC), and (MTFN) experienced financial distress, while according to Zmijewski the companies were non-distressed. so that based on the results of testing and discussion in this study, the advice given is for companies that are bankrupt, management companies must find the best way to improve business performance as soon as possible, and advice that can be given to investors, namely investors must be more selective in choosing companies to invest in, especially those with good financial performance. So that investors can invest their funds properly.